How Does the Corona Virus Strengthen Authoritarianism in Hungary? - Endre Borbáth (WZB Berlin Social Science Center, 2020)
The fight against Covid-19 as a political opportunity: Rising authoritarianism in crisis-hit Hungary.
Keywords: 300; authoritarian system; contagious disease; Coronavirus; COVID-19; Hungary; epidemic; polarization; political impact